Which Sugar to Take and How Much to Take? Two Distinct Decisions Mediated by Separate Sensory Channels - Kohatsu, Soh; Tanabe, Noriko; Yamamoto, Daisuke; Isono, Kunio (Frontiers in Molecular Neuroscience, 2022)
In Drosophila melanogaster, gustatory receptor neurons (GRNs) for sugar taste coexpress various combinations of gustatory receptor (Gr) genes and are found in multiple sites in the body. To determine whether diverse sugar GRNs expressing different combinations of Grs have distinct behavioral roles, we examined the effects on feeding behavior of genetic manipulations which promote or suppress functions of GRNs that express either or both of the sugar receptor genesGr5a (Gr5a+ GRNs) and Gr61a (Gr61a+ GRNs). Cell-population-specific overexpression of the wild-type form of Gr5a (Gr5a+) in the Gr5a mutant background revealed that Gr61a+ GRNs localized on the legs and internal mouthpart critically contribute to food choice but not to meal size decisions, while Gr5a+ GRNs, which are broadly expressed in many sugar-responsive cells across the body with an enrichment in the labella, are involved in both food choice and meal size decisions. The legs harbor two classes of Gr61a expressing GRNs, one with Gr5a expression (Gr5a+/Gr61a+ GRNs) and the other without Gr5aexpression (Gr5a−/Gr61a+ GRNs). We found that blocking the Gr5a+ class in the entire body reduced the preference for trehalose and blocking the Gr5a- class reduced the preference for fructose. These two subsets of GRNsare also different in their central projections: axons of tarsal Gr5a+/Gr61a+ GRNs terminate exclusively in the ventral nerve cord, while some axons of tarsal Gr5a−/Gr61a+ GRNs ascend through the cervical connectives to terminate in the subesophageal ganglion. We propose that tarsal Gr5a+/Gr61a+ GRNs and Gr5a−/Gr61a+ GRNs represent functionally distinct sensory pathways that function differently in food preference and meal-size decisions.